Targeted Treatment Options in Mastocytosis - Vaes, Mélanie; Benghiat, Fleur Samantha; Hermine, Olivier (Frontiers in Medicine, 2017)
Mastocytosis refers to a heterogeneous group of disorders resulting from the clonal proliferation of abnormal mast cells and their accumulation in the skin (cutaneous mastocytosis when only in the skin, CM) or in various organs (systemic mastocytosis, SM). This leads to a wide variety of clinical manifestations resulting from excessive mediator release in CM and benign forms of SM (indolent SM, ISM) and from tissue mast cell infiltration causing multiorgan dysfunction and failure in more aggressive subtypes (aggressive SM, ASM, or mast cell leukemia, MCL). In addition, SM may be associated with haematological neoplasms (AHN). While treatment of ISM primarily aims at symptom management with anti-mediator therapies, cytoreductive and targeted therapies are needed to control the expansion of neoplastic mast cells in advanced forms of systemic mastocytosis, in order to improve overall survival. Mast cell accumulation results from a gain-of-function mutation (mostly the D816V mutation) within the KIT tyrosine kinase domain expressed by mast cells and additional genetic and epigenetic mutations may further determine the features of the disease (ASM and AHN). Consequently, tyrosine kinase inhibitors and targeted therapies directed against the oncogenic signalling machinery downstream of KIT are attractive therapeutic approaches. A better understanding of the relative contribution of these genetic and epigenetic events to the molecular pathogenesis of mastocytosis is of particular interest for the development of targeted therapies and therefore to better chose patient subgroups that would best benefit from a given therapeutic strategy.